Demografic analysis of biopesticide effects on the two-spotted spider mite (Acari: Tetranychidae) following egg treatment (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
The effects of biopesticide products based on oxymatrine, azadirachtin and Beauveriabassiana (strain ATCC 74040) on demographic parameters of the two-spotted spider mite,Tetranychus urticaeKoch (Acari: Tetranychidae), were evaluated in laboratory bioassays. Thebiopesticides were applied by spraying 24 h old eggs laid on bean leaves, using the followingconcentrations: 50 μl/l (oxymatrine-based product), 0.75 g/l (azadirachtin-based product)and 3 ml/l (B. bassiana-based product). These concentrations were within 95% confidencelimits of the LC50s estimated in acute toxicity bioassays. The mites that hatched from treatedeggs completed their juvenile development on the same leaf discs, i.e. the toxic effect wascaused by topical treatment and residual exposure. When the surviving females enteredtheir preovipositional period, cohorts of 40 control and 40 treated females were transferredto untreated leaf discs (1 female/disc). Females were transferred daily to new discs untilthe death of the last one. Using the data on their age-specific survival and age-specificfertility (production of female offspring), the following demographic parameters wereestimated: gross reproductive rate (GRR), net reproductive rate (R0), intrinsic rate of increase(rm), finite rate of increase (λ), and mean generation time (T). The biopesticides significantlyaffected these demographic parameters in females that survived treatments. All threebiopesticides significantly reduced the GRR and R0 values. In the bioassays with oxymatrineandazadirachtin-based products, the rm and λ values were reduced by 22% and 5%, and16% and 4%, respectively, due to reduced survival and fertility, as well as extended juveniledevelopmental time of females that survived treatment, compared to control females. Inthe bioassay with the B. bassiana-based product, the rm and λ values were reduced by 7%and 2%, respectively, mostly due to the reduced survival of treated females. The oxymatrineandazadirachtin-based products significantly extended, while B. bassiana-based productreduced the T values.
Keywords: T. urticae; B. bassiana; azadirachtin; oxymatrine; sublethal effects; life tables